Testing-adjusted chlamydia notification trends in New South Wales, Australia, 2000 to 2010 - Michelle Cretikos; Darren Mayne; Roderick Reynolds; Paula Spokes; Daniel Madeddu (World Health Organization Regional Office for the Western Pacific, 2014)
Introduction: Between 2005 and 2010, Australian notification rates for chlamydia infection increased by 64% from 203 to 333 per 100 000 population. Interpreting this trend is difficult without examining rates and local patterns of testing. We examined the effect of adjusting for local testing rates on chlamydia notification trends in New South Wales (NSW), Australia from 2000 to 2010. Methods: We used testing data for NSW residents for Medicare Benefits Schedule items for chlamydia from 1 July 1999 to 30 June 2005 and 1 July 2007 to 30 June 2010. This data set excluded testing by public sector laboratories. We also obtained laboratory-confirmed genital chlamydia notifications in NSW residents for 1 July 1999 to 30 June 2010 and excluded notifications from public laboratories. We used negative binomial regression to assess trends in chlamydia notification rates by age and sex after adjusting for local government area (LGA)-level Medicare-funded testing rates, socioeconomic disadvantage, remoteness and Medicare provider density. Results: Testing-adjusted rates of chlamydia notifications declined by 5.2% per annum (rate ratio [RR] = 0.95, 95% confidence interval (CI) = 0.93-0.96) for women overall, and 2.3% (RR = 0.98, 95% CI = 0.96-1.00) and 5.0% per annum (RR = 0.95, 95% CI = 0.93-0.98) for men in LGAs with moderate and high densities of Medicare providers, respectively. Notification rates remained stable for men in low Medicare provider density LGAs (RR = 1.01, 95% CI = 0.96-1.07). Discussion: It is likely that increased testing for chlamydia has driven increases in chlamydia notification in NSW over the last decade. Notification data provide no evidence for a general increase in the prevalence of chlamydia in the NSW community for this period. Notification-based chlamydia surveillance should be routinely adjusted for local testing rates.